The ability to predict personality factors with a tendency to violence and its relationship to family security for a sample of the Kasbah of the capital, Amman - AL- Tarawneh, Ishraq Yousef; Al- Manaseer, Noor Elayyan; Banitaha, Nuseibah Mohammad (Journal of Educational and Psychological Sciences, 2021)
The present study aimed to reveal the extent to which personality factors predict the tendency towards violence and its relationship to family security, and the study adopted the predictive, relational, descriptive approach. The study sample consisted of (422) fathers aged between (55- 30) years from Al Mazar area in Karak Governorate, Jordan. To achieve the objectives of the study, the personality factors scale was used, the development of two scales (tendency towards violence and family security), and indicators of honesty and consistency were found and applied to the study individuals. A percentage (0.267) of the explained variance of the tendency towards violence and that the factor of openness to experience and alertness of conscience explained in its society a percentage (0.189) of the variance explained by family secure, The researcher presented a set of recommendations, including the necessity of conducting educational awareness programs for parents with methods of correct dealing and socialization, managing violence, developing counseling programs for parents in particular and families in general focusing on awareness of the characteristics of personality factors and their impact on family stability, holding workshops and organizing awareness campaigns for communities. The Arabic language in general, and the Jordanian in particular, and the definition of the impact of violence and its threat to family security and stability.
Keywords: Personal factors; The tendency to violence; family security